Transferência de tecnologia e atividades de extensão universitária: análise do projeto de capacitação de pequenos produtores de cachaça do estado de São Paulo - Barboza, Ricardo Augusto Bonotto [UNESP] (2011)
The objective of this research was to show that the transfer of technology, when conducted by a university extension activity, presents effective results. To that end, we evaluated the economic gains made by producers of rum that had adopted the technique of aging, a technique that has been studied by the Department of Foods and Nutrition, Faculty of Pharmaceutical Sciences, UNESP / Araraquara and disseminated to producers of rum from the project Training of Small Cachaça of São Paulo. To conduct research, and a literature review traced a history of the project and finally made a field survey with cachaça producers participating in the project. The study proved the end of its economic gains with the aging of the product by smallholders proving, in this case, the efficiency of the process of technology transfer conducted by an extension project